Information rights: A jurisprudential audit - Rajan, Amitabh (2009)
Contemporary transparency advocates typically draw connections between their efforts and the beginnings of modern liberal democratic theory in order to make the argument that open government is an essential element of a functional democracy. Transparency proponents also cite instrumental reasons for imposing disclosure requirements on governments. To appreciate this point fully, it is to be realised that, along with the ethic of discourse (which makes law reflexive), the processes too have to be robust and vibrant to serve citizens. No interest can have the status of a `right' unless it has an intrinsic worth high enough in priority to alleviate the lifeworld. Information Rights arte `instruments of action' for transparent governance, but instruments of action with tremendous potential for the human good. Legislatures reconcile legitimate competing interests, and courts interpret legislative output. The phenomenon, however, needs stronger conceptualization to determine the role of civil society. In an attempt to explore the gap between law and justice, this article proposes to record discursive rationality in law making, and, then see how law thinks through case laws. - Reproduced.
Keywords: Right to information